Desenvolvimento e aplicação de um protocolo osteopático de tratamento para bebês com refluxo - Gemelli, Mauro (2014)
The prevalence of gastroesophageal reflux disease (GERD) in infants in Brazil is about 11.5% to 18,2%, similar to international data, bringing symptoms that can be perpetuated into childhood and adolescence. Current treatment protocols are medicated summary, and few studies have reported evidence for complementary therapies in the treatment of reflux. Osteopathy could be used in this context to treat the causes of reflux, however, studies evaluating Osteopathic Protocols Treatments (OPT) are limited and are not specific for this diagnosis. The objective of this study was to develop and evaluate the application of a OPT developed for infants less than one year through a quantitative method. A longitudinal descriptive study of 59 babies aged under one year of age diagnosed with reflux and in a drug treatment was performed. Initially all were evaluated with I-GERQ-R questionnaire. Thirty- three children were selected for group A, which was submitted to OPT parallel to pharmacological treatment for two months or until it reaches a minimum score on the questionnaire, whichever came first. Group B was accompanied by the same period of two months and after that being re-evaluated. Data collected from the questionnaire and the associated symptoms of colic and cough were analyzed. In group A, the initial average score I-GERQ-R was 14.57 ±3.65 and 1.39 ±2.09 points at the end (p = 0.001). In group B these values were 17.23 ±4.78 and 8.46 ±7.41 points, featuring a stay of group B in the diagnosis of reflux (score>7) despite improvement with statistical significance (p = 0.043). In group A, 13 subjects reached the final score zero ("0"), while in group B no individual reached this score. Reduced use of medication in group A was 75.76% while in group B this reduction was only 11.54%. The improvement in group A occurred at a mean time of 28.76 ±11.43 days, regardless of age, where the average number of sessions was 3.91 ±0.80. The symptom of vomiting improved significantly in group A (p = 0.001) but not in group B (p = 0.063). The symptom of heartburn showed a significant improvement in both groups A and B (p = 0.001 and p = 0.002 respectively), as well as hiccup (p = 0.001 and p = 0.001 respectively). The symptom of crying showed significant improvement in group A (p = 0.001), but not for group B (P = 0.123). Likewise, choking episodes exhibited statistically significant reduction in group A (p = 0.001) and not in group B (p = 0.105). Coughing in the group A was reduced by 94.75% (p=0,001) and 75% in colic (p=0,001). In group B the cough remained with the same incidence (14 cases) (p=1,000) and colic increased significantly from nine to 17 cases (p=0,008). Therefore, it is concluded that the proposed OPT was effective in reducing symptoms of reflux in infants and symptoms of cough and colic associated in an approximate 29 days to levels close to zero, time lower than that described in the literature. It is understood that the protocol has reached the causal mechanisms of GER, and therefore the association of OPT with a medication treatment may be suggested in the approach of GER in infants less than one year old.